Increasing polymyxin resistance in clinical carbapenem-resistant Klebsiella pneumoniae strains in China between 2000 and 2023 - Miaomiao Xie; Yanyan Zhang; Kaichao Chen; Ning Dong; Hongwei Zhou; Yonglu Huang; Congcong Liu; Edward Wai-Chi Chan; Sheng Chen; Rong Zhang (Communications Medicine)
Abstract Background Development of polymyxin resistance in carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a severe challenge to public health. Here we aimed to perform a retrospective study of prevalence and molecular characteristics of polymyxin-resistant CRKP strains. Methods 4455 clinical CRKP strains from 18 provinces in China during 2000 to 2023 were collected. Polymyxin-resistant CRKP strains were subjected to antimicrobial susceptibility testing, whole genome sequencing and bioinformatic analysis. Molecular mechanisms underlying the polymyxin resistance in CRKP were analyzed. Results Here we show that polymyxin-resistant CRKP emerge initially in 2014, prevalence of such strains then increase steadily over the years, reaching a rate of 9.86% in 2023. In total, 112 polymyxin-resistant CRKP isolates are identified. Antimicrobial susceptibility tests show that all polymyxin-resistant CRKP are resistant to commonly used antibiotics, yet most isolates remain susceptible only to ceftazidime-avibactam and tigecycline. Predominant polymyxin resistance mechanism in CRKP is mutations in mgrB (59/112), which commonly involves disruption of mgrB by insertion of elements such as ISKpn26 (20/59), IS903B (14/59), and ISKpn14 (9/59). Phylogenetic analysis reveals frequent clonal dissemination of polymyxin-resistant CRKP within the same hospital and even among different hospitals in neighboring provinces. pLVPK-like virulence plasmids are detected in 46 isolates, such strains are therefore categorized as polymyxin and carbapenem-resistant hypervirulent K. pneumoniae which may cause infections with high mortality. Conclusions Our results highlight frequent clonal transmission of polymyxin-resistant CRKP within hospitals. Continuous surveillance of polymyxin resistance among CRKP should be implemented to prevent further dissemination of such strains in clinical settings in China.